The state of renin-aldosterone system in patients with resistant arterial hypertension - О. H. Оbertynska (Zaporožskij Medicinskij Žurnal)
Purpose. The understanding of pathophysiology and clinical characteristics of resistant hypertension (RH) remains elusive. The aim of this work was to study the relationships between clinical course of RH and levels of renin and aldosterone (AS).